PERILAKU PENCARIAN PENGOBATAN MALARIA PADA ANAK BALITA DI WILAYAH KERJA PUSKESMAS SANANA KABUPATEN KEPULAUAN SULA - , Siti Hawa Kharie; , dr. Ova Emilia, Sp.OG(K)., PhD, M. M.Ed ([Yogyakarta] : Universitas Gadjah Mada, 2012)
Background: Malaria is one of infectious diseases that becomes a public health problem and greatly affects mortality and morbidity for infants, toddlers (under-five) and giving birth mothers. In addition, it can directly cause anemia and lower work productivity. Kepulauan Sula District is included in an area with high malaria cases. Health-seeking for children under five years old is done in many ways, such as seeking treatment into health services, traditional remedy, taking free-marketed drugs without any prescription or doing nothing for the child. Objective: To determine the relationship of mothers with children under five years old suffering from malaria to treatment seeking behavior in Kepulauan Sula District. Methods: This was an observational study using a cross-sectional design with quantitative and qualitative approaches. The method used simple random sampling. The research subjects were mothers with under-five children suffering from malaria positive as many as 90 people. Analysis of the data used univarible analysis with descriptive statistics, bivariable analysis with chi square, multivariable analysis with logistic regression and qualitative analysis in distributive form and conclusions. Results: There was a relationship between mothersâ education level and treatment-seeking behavior (RP = 2.64, 95% CI = 1.02 to 6.82), family incomes and treatment-seeking behavior (RP = 2.19, 95% CI = 1.05 to 4.56), trust and treatment-seeking behavior (RP = 2.05, 95% CI = 1.14 to 3.68), access to health care coverage and treatment-seeking behavior (RP = 2.14, 95% CI = 1.18 to 3.90), p perceptions on the danger of malaria and treatment-seeking behavior (RP = 2.20, 95% CI = 1.00 to 4.83), and perceptions on information about malaria and treatment-seeking behavior (RP = 2.31, 95% CI = 1.05 to 5.07). Conclusion: There was a significant relationship between maternal education level, household income, level of trust, access to health care coverage, perception on the danger of malaria and perception on information about malaria and treatment-seeking behavior among underfive children in Kepulauan Sula District.